The effect of direct access to CT scan in early lung cancer detection: an unblinded, cluster-randomised trial. Issue 1 (December 2015) - Guldbrandt, Louise; Fenger-Grøn, Morten; Rasmussen, Torben; Rasmussen, Finn; Meldgaard, Peter; Vedsted, Peter
Abstract Background Lower lung cancer survival rates in Britain and Denmark compared with surrounding countries may, in part, be due to late diagnosis. The aim of this study was to evaluate the effect of direct access to low-dose computed tomography (LDCT) from general practice in early lung cancer detection on time to diagnosis and stage at diagnosis. Methods We conducted a cluster-randomised, controlled trial including all incident lung cancer patients (in 19-month period) listed with general practice in the municipality of Aarhus (300, 000 citizens), Denmark. Randomisation and intervention were applied at general practice level. A total of 266 GPs from 119 general practices. In the study period, 331 lung cancer patients were included. The intervention included direct access to low-dose CT from primary care combined with a 1 h lung cancer update meeting. Indication for LDCT was symptoms or signs that raised the GP's suspicion of lung cancer, but fell short of satisfying the fast-track referral criteria on red flag' symptoms. Results The intervention did not significantly influence stage at diagnosis and had limited impact on time to diagnosis. However, when correcting for non-compliance, we found that the patients were at higher risk of experiencing a long diagnostic interval if their GPs were in the control group. Conclusion Direct low-dose CT from primary care did not statistically significantly decrease time to diagnosis or change stage at diagnosis in lung cancer patients. Case finding with direct access to LDCT may be an alternative to lung cancer screening. Furthermore, a recommendation of low-dose CT screening should consider offering symptomatic, unscreened patients an access to CT directly from primary care. Trial registration www.clinicaltrials.gov, registration ID numberNCT01527214 .